The Hegemony Of The Coal Mining Corporation, The Destruction Of The Kutai Rice Barn Center And The Damage To The Living Space Of Transmigrants - Sri Murlianti; Argyo Demartoto; Merah Johansyah; Sarah Agustiorini (Eduvest - Journal of Universal Studies, 2022)
Kerta Buana Village, became the location for transmigrants from Bali, Lombok (NTB) and a few local transmigrants in 1980. This village later grew to become part of the main rice granary area of ​​Kutai Kartanegara Regency, as well as being known as the Bali Village of East Kalimantan. Kerta Buana is also known as the Pancasila Village, because of the harmony of the villagers with the background of 2 different dominant religions, Balinese transmigrants are Hindu and Lombok Muslim transmigrants. However, at present Kerta Buana Village has suffered severe damage to life, has changed its face into a village surrounded by coal mines, surrounded by 14 mining pits, agricultural productivity is low and a class of farmers without rice fields has emerged. This article analyzes how a transmigrant village that was once known as part of the district's food barn has now turned into a village surrounded by mining. Data was collected by in-depth observation, in-depth interviews with 16 key informants from each transmigrant group and repeated focus group interviews. Antonio Gramsci's concept of hegemony is used to explain how company power builds historical blocks, hegemony villagers with extractive economic ideology so that villagers agree to massive coal exploration around the village. The results show that companies use corporate and government institutions, community leaders, security forces and even local communities to lead transmigrants to obey the